Comparison of the flexural strength of polymethyl methacrylate resin reinforced with multiwalled carbon nanotubes and processed by conventional water bath technique and microwave polymerization - Surabhi Somkuwar; Sunil Kumar Mishra; Benaiffer Agrawal; Rupali Choure (Wolters Kluwer Medknow Publications, 2017)
Purpose: This in vitro study was done to compare the flexural strength of polymethyl methacrylate resin reinforced with multiwalled carbon nanotubes (MWCNTs) and processed by conventional water bath technique and using microwave energy. Materials and Methods: A total of 180 acrylic resin specimens measuring 65 mm × 10 mm × 2.5 mm were fabricated, with conventional water bath groups and microwave group having ninety specimens each. Ninety specimens were divided into thirty specimens as control and subgroups containing 0.025% MWCNTs and 0.050% MWCNTs with thirty specimens each. The specimens were tested for flexural strength by three-point bending test on universal testing machine. The statistical analysis was done using Student's t-test and one-way analysis of variance, and the intercomparison between each group was done using Tukey's post hoc analysis. Results: The mean flexural strength of specimens cured by water bath technique was 95.563 MPa and microwave technique was 118.416 MPa. Control Group B possesses highly significant increase in flexural strength than Control Group A with P < 0.01. Unpaired Student's t-test showed that Subgroup B1 and Subgroup B2 possess highly significant increase in flexural strength than Subgroup A1and Subgroup A2. Conclusion: Heat polymerized denture base resin with and without reinforcement of MWCNTs and polymerized by microwave technique possess higher flexural strength than heat polymerized fiber reinforced denture resin polymerized by water bath technique. MWCNTs could be used as an effective reinforcement material for denture base resin polymerized by either water bath technique or microwave energy.